FATE AND EFFECTS OF PHOSPHORUS ADDITIONS IN SOILS UNDER N2-FIXING RED ALDER - Compton Ja.E.; Cole D.W. (My University, 2001)
Soil phosphorus (P) dynamics are controlled by the interaction of geochemical, biochemical and biological processes. Changes in species composition or management could alter the relative importance of these processes. We examined soil P dynamics in two plantations of N2-fixing red alder (Alnus rubra) by determining the fate and effects of added fertilizer P. History of the plantations varied such that sites were previously occupied by 60-yr-old stands of alder or non-fixing Douglas-fir (Pseudotsuga menziesii). Without fertilization, the soil with a longer period of alder influence had more organic P (Po) and less sorbed inorganic P (Hydroxide- and Bicarb-extractable Pi). Fertilization increased soil total P, and 88% of the fertilizer was Soil phosphorus (P) dynamics are controlled by the interaction of geochemical, biochemical and biological processes. Changes in species composition or management could alter the relative importance of these processes. We examined soil P dynamics in two plantations of N2-fixing red alder (Alnus rubra) by determining the fate and effects of added fertilizer P. History of the plantations varied such that sites were previously occupied by 60-yr-old stands of alder or non-fixing Douglas-fir (Pseudotsuga menziesii). Without fertilization, the soil with a longer period of alder influence had more organic P (Po) and less sorbed inorganic P (Hydroxide- and Bicarb-extractable Pi). Fertilization increased soil total P, and 88% of the fertilizer was accounted for in the surface mineral soil (0-15 cm). Sorbed Pi was the major sink for fertilizer P (55-60%), independent of site history. Although Po was 35-70% of soil P in unfertilized plots, added P did not accumulate as Po. Neither site history nor P addition influenced phosphatase activity. Fertilization increased decomposition during incubation of the organic horizon, suggesting that late-stage decomposition is P-limited in these N-rich soils. On the time-scale of a few years, geochemical sorption and desorption of inorganic P were the most important processes controlling the distribution of added P. Organic P accumulation is expected to occur over a longer time frame, linked to the production and turnover of organic matter.
Keywords: DECOMPOSITION; ELEMENT INTERACTIONS; NITROGEN FIXATION; ORGANIC PHOSPHORUS; PHOSPHORUS FERTILIZATION; PHOSPHORUS FRACTIONS; RED ALDER